Total phenols, stilbene and antioxidative activity in Babić and Plavac mali wines : eficiency of pectolytic enzymes - Alpeza, Ivana (Array, 2019)
Special importance of wine polyphenols have been associated with the bioactive compounds because of their benefits on human health. Research of acceptable and safe technological processes that would enable the production of wines with a higher content of such compounds is a need and a challenge. For this reason, the aim of this study was to investigate the influence of commercial pectolytic enzymes to total phenols (UF), stilbene and antioxidative activity (AA) of Babić and Plavac mali red wines, originated from middle quality localities. Two enzymatic product with different properties were used: pectinase with celulase and hemicelulase additional activity (E1) and pectinase with inactive yeast cells (E2), in comparison to maceration without egzogenous enzymes (control, K). The quality parameters were analysed in different production stages; from the end of maceration and fermentation to wine after the second decanting and bottling. Both products affected to those quality parameters. Maceration with pectolytic enzymes (E1) provided the best extraction and production of wines with the significant highest concentrations of total phenols of both varieties, in both years. The highest values of AA were obtained in wines of treatmant E1, in both years of research and for both varieties. Significant differences were obtained for both varieties, but not in both years. Maceration with egzogenous enzymes effected enrichment of wines with stilbenes, resveratrol and piceid particularly, however the significant differences did not obtained in both years of research. The differences between varieties were noted: while the resveratrol dominated in Plavac mali wines, higher proportion were obtained for piceid in Babić wines. Despite relatively better results in comparison to control, the use of product E2 was not found to be beneficial; significant differences were not confirmed for any variety during both years of the experiment.